Perturbation of the immune cells and prenatal neurogenesis by the triplication of the Erg gene in mouse models of Down syndrome. (4th July 2019) - Ishihara, Keiichi; Shimizu, Ryohei; Takata, Kazuyuki; Kawashita, Eri; Amano, Kenji; Shimohata, Atsushi; Low, Donovan; Nabe, Takeshi; Sago, Haruhiko; Alexander, Warren S.; Ginhoux, Florent; Yamakawa, Kazuhiro; et al.
Abstract: Some mouse models of Down syndrome (DS), including Ts1Cje mice, exhibit impaired prenatal neurogenesis with yet unknown molecular mechanism. To gain insights into the impaired neurogenesis, a transcriptomic and flow cytometry analysis of E14.5 Ts1Cje embryo brain was performed. Our analysis revealed that the neutrophil and monocyte ratios in the CD45‐positive hematopoietic cells were relatively increased, in agreement with the altered expression of inflammation/immune‐related genes, in Ts1Cje embryonic brain, whereas the relative number of brain macrophages was decreased in comparison to wild‐type mice. Similar upregulation of inflammation‐associated mRNAs was observed in other DS mouse models, with variable trisomic region lengths. We used genetic manipulation to assess the contribution of Erg, a trisomic gene in these DS models, known to regulation hemato‐immune cells. The perturbed proportions of immune cells in Ts1Cje mouse brain were restored in Ts1Cje‐Erg +/+/Mld2 mice, which are disomic for functional Erg but otherwise trisomic on a Ts1Cje background. Moreover, the embryonic neurogenesis defects observed in Ts1Cje cortex were reduced in Ts1Cje‐Erg +/+/Mld2 embryos. Our findings suggest that Erg gene triplication contributes to the dysregulation of the homeostatic proportion of the populations of immune cells in the embryonic brain and decreased prenatal cortical neurogenesis in the prenatal brain with DS.